Analisis Daya Saing Agribisnis Kopra di Kecamatan Lambai Kabupaten Kolaka Utara - Hasballah Hasballah; Saediman Saediman; Ilma Sarimustaqima Rianse (Jurnal Sosio Agribisnis, 2021)
This study aimed to analysis the level of comparative and competitive advantage of copra agribusiness, and to analyze the inpact of government’s policy on the comparative and competitive advantage of copra agribusiness in Lambai District, North Kolaka Regency. The study was conducted from May to November 2020. The population consisted of 150 coconut/copra farmers. The sampling technique was carried out by cluster random sampling. Determination of the number of samples using the Slovin formula, with a total sample of 109 coconut/copra farmers. The data collected includes: inputs and outputs, private prices and shadow prices of copra agribusiness inputs and outputs. The study used the Policy Analysis Matrix (PAM) to analysze data. The result of the study showed that copra agribusiness has a high level of competitiveness as shown by the Domestic Resources Cost Ratio (DRCR) the value of 0,10 and Private Cost Ratio (PCR) value of 0,15.  Regarding government’s policy on output, it was revealed that farmers do not gain benefits from the policy as shown by the Nominal Protection Coefficient on Output (NPCO) value of 0,96.  The government's policy on tradable inputs has created efficiency in copra agribusiness activities as indicated by the Nominal Protection Coefficient on input (NPCI) value of 0.39. The government's policy on input-output is not in favor of farmers because it has reduced the profits of the copra agribusiness as indicated by the Profit Coefficient PC value of 0.93.Keywords: competitiveness; copra agribusiness; Policy Analisys Matrix (PAM)